2000
DOI: 10.1007/s007740050016
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cervical and trochanteric fractures of the proximal femur in 1994 in Tangshan, China

Abstract: The purpose of this study was to determine the incidence of cervical and trochanteric fractures of the proximal femur in 1994 in Tangshan City, China. There are many reports on hip fracture incidence in many countries, suggesting that there are many factors affecting hip fractures. We visited 15 hospitals with an orthopaedic department within Tangshan City, and reviewed the medical records and radiographs of all patients with hip fractures occurring between January 1 and December 31, 1994. The population of Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…Because of its lower cross-sectional area and moments of inertia, coupled to large bending moments, the femoral neck could be expected to be the most likely site of fracture. This prediction is supported by studies in humans and other mammals (Crawford and Fretz, 1985;Embertson et al, 1986;Zhang et al, 2000;Harasen, 2003) and our experimental results: all femora fractured proximally at the neck, rather than in the shaft.…”
Section: Fracture Strength and Naturalistic Loadingsupporting
confidence: 87%
See 1 more Smart Citation
“…Because of its lower cross-sectional area and moments of inertia, coupled to large bending moments, the femoral neck could be expected to be the most likely site of fracture. This prediction is supported by studies in humans and other mammals (Crawford and Fretz, 1985;Embertson et al, 1986;Zhang et al, 2000;Harasen, 2003) and our experimental results: all femora fractured proximally at the neck, rather than in the shaft.…”
Section: Fracture Strength and Naturalistic Loadingsupporting
confidence: 87%
“…Right femora were used for morphometric measurements and mechanical testing, and left femora were scanned using microcomputed tomography (µCT). The femur was chosen for detailed study because it is subject to the most direct loading from the axial skeleton, and the proximal femur is the site of most femoral fractures (Crawford and Fretz, 1985;Embertson et al, 1986;Zhang et al, 2000;Harasen, 2003).…”
Section: Specimen Preparationmentioning
confidence: 99%
“…In Asia, we found that rates from Hong Kong [25,51] and Taiwan [47] tended to be among the highest, whereas studies from mainland China [25,59,60] were among the lowest. Interestingly, Middle Eastern countries had both the highest (Shiraz, Iran [58]) and lowest (Beirut, Lebanon [45]) rates in Asia.…”
Section: Results Of Cross-national Comparisonmentioning
confidence: 66%
“…In modern epidemiological studies, intracapsular fractures are generally more common than extracapsular fractures (Kannus et al, 1996;Michaëlsson et al, 1999;Zhang et al, 2000), but not always (Maghraoui et al, 2005). These two types of hip fracture are usually considered together in aetiological studies (Michaëlsson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%